Information & Media Literacy – eLearning at NTU Library - JAYAPAL, Umarani (Institutional Knowledge at Singapore Management University, 2020)
Information & Media Literacy is a fully interactive and animated online eLearning program for all freshmen in NTU. One of our bite-sized game based units covers the topic of Identifying Fake News where students are not only taught the identifying characteristics of and consequences of spreading Fake News but also get to experience real life scenarios to apply the knowledge learnt.